2004
DOI: 10.1177/089686080402400507
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin and Ciprofloxacin: Systemic Antibiotic Administration for Peritoneal Dialysis-Associated Peritonitis

Abstract: Objectives Peritonitis due to peritoneal dialysis (PD) is best treated empirically while waiting for the results of the dialysate culture. Thus, antibiotic therapy must cover both gram-positive and gram-negative micro-organisms. First, over a period of 9 years in a multicenter study we evaluated the efficiency of a vancomycin and ciprofloxacin combination given as the first-line treatment protocol for PD peritonitis. Second, we evaluated whether a systemic route of administration of the antibiotics could be an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 33 publications
0
32
0
1
Order By: Relevance
“…Moreover, IP dosing avoids venipuncture and could be done by the patient at home after appropriate training. Although IV vancomycin is reasonably successful as empirical gram-positive coverage ( 237 ), previous studies have shown that IV vancomycin resulted in a significantly higher rate of primary treatment failure than IP administration ( 203 , 305 ). Intraperitoneal antibiotics should be added using sterile technique, such as placing povidone iodine, rubbing with alcohol 70% strip, or chlorhexidine on the medication port for 5 minutes prior to insertion of the needle through the port.…”
Section: Initial Presentation and Management Of Peritonitismentioning
confidence: 99%
“…Moreover, IP dosing avoids venipuncture and could be done by the patient at home after appropriate training. Although IV vancomycin is reasonably successful as empirical gram-positive coverage ( 237 ), previous studies have shown that IV vancomycin resulted in a significantly higher rate of primary treatment failure than IP administration ( 203 , 305 ). Intraperitoneal antibiotics should be added using sterile technique, such as placing povidone iodine, rubbing with alcohol 70% strip, or chlorhexidine on the medication port for 5 minutes prior to insertion of the needle through the port.…”
Section: Initial Presentation and Management Of Peritonitismentioning
confidence: 99%
“…The pooled proportion resolution rate from nine studies [ 55 , 76 , 85 , 92 , 95 98 ] with 138 episodes was 68% (95% CI 0.50–0.85) for a quinolone (Figure 5 ). For ceftazidime, the resolution rate was 61% (95% CI 0.53–0.70) from three studies [ 68 , 56 , 98 ] with 117 episodes (Figure 6 ), and for aminoglycosides it was 65% (95% CI 0.51–0.77) from nine studies [ 55 , 57 , 62 , 68 , 76 , 85 , 90 , 97 , 98 ] with 211 episodes (Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Se debe tener cuidado al examinar el líquido de drenaje por el catéter, el cual podrá ser turbio o incluso purulento, pero nunca intestinal. Se puede administrar una terapia empírica con vancomicina y ciprofloxacino [26], sin embargo idealmente se administrara una antibiótico-terapia dirigida mediante el cultivo [27], dicho tratamiento podrá administrarse IV o intraperitoneal [28], cabe recordar que el antibiótico intraperitoneal podrá causar una reacción inflamatoria en la capa mesotelial subdiafragmática condicionando un pobre funcionamiento si se considera la recolocación del catéter.…”
Section: Complicacionesunclassified